Evaluasi Komparatif Penanda CDS ITS1, ITS2, dan LEAFY (LFY) untuk Diskriminasi Spesies pada Asteraceae - Aulia Fitriana Ardhyatul Jannah; Ira Erdiandini; Mufidah; Thoriq Ahmad Syauqy; Aqwin Polosoro (Buitenzorg: Journal of Tropical Science, 2026)
Asteraceae is one of the largest and most diverse angiosperm families, making species identification challenging, especially among closely related taxa with overlapping morphological characters. This study evaluated the performance of ITS1, ITS2, and the coding sequence of the LEAFY (LFY) gene as molecular markers for discriminating selected Asteraceae species and assessing relationships at the genus, tribe, and subfamily levels. Publicly available sequences were retrieved from NCBI databases and curated based on taxonomic identity, marker annotation, sequence quality, and accession consistency. The ITS1, ITS2, and LFY coding sequence (CDS) datasets were aligned separately using MUSCLE in MEGA, followed by sequence variation analysis, Maximum Likelihood phylogenetic reconstruction, and pairwise genetic distance analysis. All three markers recovered broad taxonomic patterns, including the clustering of Chrysanthemum species and the separation of more distant genera such as Helianthus, Tagetes, Erigeron, Cynara, and Lactuca. LFY CDS showed the highest absolute number of variable sites and parsimony-informative sites, followed by ITS2 and ITS1. ITS2 provided slightly greater phylogenetic information than ITS1, while LFY CDS provided an independent nuclear coding signal that complemented the ribosomal ITS markers. Overall, each marker contributed useful phylogenetic information for assessing taxonomic relationships within Asteraceae.   Keywords: Asteraceae, ITS1, ITS2, LFY, DNA barcoding, species discrimination, phylogenetic analysis.